Triggering coverage under a liability policy / Rosmi Yuhasni Mohamed Yusuf - Mohamed Yusuf, Rosmi Yuhasni (Universiti Teknologi MARA Cawangan Pahang, 2003)
Two widely differing approaches are used by insurers to determine coverage when writing liability insurance. The difference centers upon the event that triggers coverage and is known as the coverage trigger. The two approaches are known as claims made and occurrence. This paper is an attempt to explain and investigate the relevancy of both mechanisms used in determining the question of coverage when a particular claim is made.